Kegiatan Pengabdian Masyarakat Mengenai Penapisan Status Gizi Siswa Sekolah Dasar Negeri Maleber, Ciherang, Jawa Barat - Alexander Halim Santoso; Edwin Destra; Farell Christian Gunaidi; Agnes Marcella; Ines Haryanto; Bobby Marshel Ancheloti Waltoni; Tosya Putri Alifia (BADAN PENERBIT STIEPARI PRESS, 2024)
The impact of nutritional status on cognitive function, academic achievement and performance, and overall productivity is substantial. Adequate nutritional status safeguards society against the detrimental effects of malnutrition, thereby preserving the collective national welfare in addition to enhancing individual well-being. The Plan-Do-Check-Action (PDCA) method is implemented by this service. The screening process entails the collection of anthropometric data, including weight, height, and body mass index. The expeditious implementation of community-based initiatives that detect nutritional disorders in their early stages can effectively mitigate the detrimental effects of malnutrition on the health of children. It is critical to incorporate a comprehensive approach that tackles determinants including socio-economic factors and promotes healthy eating practices in order to effectively combat malnutrition and facilitate optimal growth and development.